Corporate hierarchy and vertical information flow inside the firm—a behavioral view - Reitzig, Markus; Maciejovsky, Boris (Strategic Management Journal, 2015)
Little is known about how corporate hierarchies influence managers' propensity to pass information upward within the firm. Two streams of literature arrive at seemingly conflicting and untested predictions. Information economists maintain that middle managers pass more suggestions up the firm's line of command as the corporate hierarchy increases in order to avoid corporate omission errors. In contrast, scholars of organizational psychology suggest that hierarchies lead to evaluation apprehension and foster a perceived lack of control among mid‐level managers, leading to their reduced willingness to, and interest in, passing information up within the organization. Drawing on field data and model‐guided experimental studies, we provide original empirical evidence for the relevance of all the mechanisms above, and we delineate the conditions under which either mechanism prevails . Copyright © 2014 John Wiley & Sons, Ltd.